Potential Supervision Consultant Contract Disputes Due to Extension of Contractor Time in DKI Jakarta Regional Government Project Based on Fidic White Book - Nuranto, Adi (ASTONJADRO, 2024)
DKI Jakarta is a province in Indonesia that has the most significant regional budget (APBD). This has led to numerous infrastructure development projects funded by the regional budget in Jakarta. Most projects in Jakarta follow a traditional document tendering process, where procurement starts with the engagement of planning consultants to design a project. After the planning documents are completed, contractor and supervision consultant services are procured concurrently. This research aims to identify the factors that result in non-extension and non-payment of supervising consultants and to determine the potential dominant disputes in supervising consultant contracts due to contractor time extension addendums, particularly in projects within the regional government environment of DKI Jakarta. The aim is to minimize the impact of such issues in the future. This research is a combined study with a sequential form. The population of this research consists of building construction projects in the province of DKI Jakarta. The sample for this research is a sports arena construction project. The respondents in this study are the project owners and the supervising consultants associated with the research project. The data will be processed using a rating evaluation method, allowing for the relative comparison of the predetermined variable categories with each other. The provisions should be based on fairness between the contracting parties. The research findings indicate that supervising consultants are entitled to time extensions and additional fees for supervision during the extended period, due to the contractor's extension of the physical implementation time based on technical considerations. The feasibility of the extension proposal is assessed through research, and the results are documented in an addendum to the contract.